Design spaces and EEG frequency band power in constrained and open design. Issue 4 (2nd October 2022) - Vieira, Sónia; Benedek, Mathias; Gero, John; Li, Shumin; Cascini, Gaetano
ABSTRACT: Design space is a common abstraction used in the investigation of design cognition. Characteristic properties of design spaces and how they change are underexplored. Design spaces can vary with the design task and its constraints, which are assumed to result in differences in neurocognitive processes. We review general cognition, creative cognition and design neurocognition EEG studies. We analyzed the brain activity of 32 professional mechanical engineers and industrial designers while performing constrained and open design tasks. The neurophysiological activations during reading the task, earliest reaction, and open externalization stages of constrained and open design are compared based on EEG frequency band power. Significant differences between constrained and open design for the beta bands were found in the earliest reaction stage. Significant differences between constrained and open design for alpha 2 and the beta bands were found in the open externalization stage. We discuss the results and relate the higher brain activity and significant differences in open design to cognitive functions of interest to design cognition. We show that EEG brain activation is sensitive to the level of constraints in designing, in particular alpha 2 and beta bands can act as proxies of the change and expansion of design spaces.